15q13.2q13.3 microdeletion syndrome with congenital stationary night blindness due to compound deletion and a missense point mutation in TRPM1 gene - Pietrasik, Justyna; Młynek, Marlena; Wiśniewska, Agata; Sielska-Rotblum, Danuta; Białecka, Magdalena; Kotlarek-Łysakowska, Marta; Chrzanowska, Krystyna; Madej-Pilarczyk, Agnieszka (Pediatria Polska - Polish Journal of Paediatrics, 2025)
The 15q13.3 microdeletion syndrome is associated with a variable phenotype, often with incomplete penetrance, characterised by psychomotor developmental delay, intellectual disability, autism spectrum disorders, and nonspecific dysmorphic features. Epilepsy, congenital heart defects, and ophthalmologic abnormalities, including strabismus and/or astigmatism, may also occur. In the case of a homozygous 15q13.3 deletion involving the TRPM1 gene, symptoms of congenital stationary night blindness additionally appear. A similar clinical effect is associated with compound damage to both copies of the TRPM1 gene, in the form of a deletion involving this gene on one allele and a point mutation in TRPM1 on the other allele. We present a patient with a complex 15q13.2q13.3 deletion and a hemizygous TRPM1 variant c.332A>G, p.Tyr111Cys, in whom neurodevelopmental symptoms coexist with congenital stationary night blindness.